STUDI PRESERVASI AKIBAT ADANYA BANGUNAN TOWER DI ATAS GEDUNG C UNIVERSITAS MUHAMMADIYAH JEMBER - Nur Muhammad Isa; Pujo Priyono; Ilanka Cahya Dewi (Universitas Muhammadiyah Jember, 2017)
The increasing demand for communications technology that is cheap and easy to force mobile phone service providers to improve mobile phone network signals. However given their land crisis that is increasing each year so that the underlying to rise and Rooftop on a building C at the University of Muhammadiyah Jember. So we need to review the interaction between the buiding and the tower to determine the effect after the addition of the tower load including the effects of an eartquake, because given the muddy located in the earthquake zone to zone 3. This study started from existing data of buildings such as the dimensions of the beam, column and plate proceed with modelig the structure before and after the existing tower to find out the results of the interactions that occur and the determine changes in the dimensions of comprehensive reinforcement occurs sothat from these data may generate recommendations that will be used to future.The result of this study showed that the effect of the earthquake was the largest factor affecting the rift, and the final result of the output value of the aplicationthat is used is SAP 2000V14 shows the value of the force in each elementof the structure and k now the strong value of the load that can be carried by the structure of the building.